What CSR Practices Lead to Sustained Competitive Advantage? The Case of Regus UK - Gardiner, Sara (2007)
Despite a desire amongst researchers to provide a convincing rationale for managers to adopt socially responsible practices (Rowley & Berman, 2000), quantitative studies evaluating the relationship between corporate social performance and financial performance have produced mixed results and failed to conclusively establish a causal link (Griffin & Mahon, 1997). This study seeks to provide such a rationale but instead considers the link between CSR and the broader strategic goal of sustained competitive advantage. It aims to identify specific CSR practices likely to exert the greatest influence on sustained competitive advantage, and to therefore provide a useful approach for management in the formulation of a CSR strategy which creates value. The research merges insights from the resource-based view of the firm, stakeholder theory and stakeholder salience theory and essentially argues that CSR practices identified through dialogue with key stakeholders to lead to enhanced reputation and employee engagement are likely to influence sustained competitive advantage. Regus, a FTSE 250 company, is used as a case study and an initial CSR strategy is proposed for them on this basis.